The verification of ethnographic data. (September 2017) - Pool, Robert
Anthropologists are increasingly required to account for the data on which they base their interpretations and to make it available for public scrutiny and re-analysis. While this may seem straightforward (why not place our data in online repositories?), it is not. Ethnographic 'data' may consist of everything from verbatim transcripts ('hard data') to memories and impressions ('soft data'). Hard data can be archived and re-analysed; soft data cannot. The focus on hard 'objective' data contributes to the delegitimizing of the soft data that are essential for ethnographic understanding, and without which hard data cannot be properly interpreted. However, the credibility of ethnographic interpretation requires the possibility of verification. This could be achieved by obligatory, standardised forms of personal storage with the option for audit if required, and by being more explicit in publications about the nature and status of the data and the process of interpretation.